2013
DOI: 10.1371/journal.ppat.1003210
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans White and Opaque Cells Undergo Distinct Programs of Filamentous Growth

Abstract: The ability to switch between yeast and filamentous forms is central to Candida albicans biology. The yeast-hyphal transition is implicated in adherence, tissue invasion, biofilm formation, phagocyte escape, and pathogenesis. A second form of morphological plasticity in C. albicans involves epigenetic switching between white and opaque forms, and these two states exhibit marked differences in their ability to undergo filamentation. In particular, filamentous growth in white cells occurs in response to a number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
98
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(106 citation statements)
references
References 68 publications
(110 reference statements)
7
98
1
Order By: Relevance
“…For example, under conditions of various environmental signals, the yeast forms of C. albicans can switch to filamentous cells (4)(5)(6)(7)(8). The reversible yeast-hypha transition regulated by a core set of transcription factors that mediate its developmental program is complex (7,(9)(10)(11)(12)(13). Hyphal formation also plays a major role in biofilm formation, which is closely linked with the propensity to cause infection and is associated with antifungal resistance (14)(15)(16).…”
mentioning
confidence: 99%
“…For example, under conditions of various environmental signals, the yeast forms of C. albicans can switch to filamentous cells (4)(5)(6)(7)(8). The reversible yeast-hypha transition regulated by a core set of transcription factors that mediate its developmental program is complex (7,(9)(10)(11)(12)(13). Hyphal formation also plays a major role in biofilm formation, which is closely linked with the propensity to cause infection and is associated with antifungal resistance (14)(15)(16).…”
mentioning
confidence: 99%
“…albicans can grow and be propagated as epigenetically distinct white-or opaque-phase cells, and an additional recent study (41) showed that opaque-phase C. albicans colonies can also assume a hyphal form under conditions of P i limitation, unlike white-phase cells, which (at least in the canonical laboratory isolates commonly used for physiological studies, such as strain SC5314) are not typically induced to express a hyphal phenotype with P i starvation as the sole nutrient limitation. The observed induction of hyphal morphogenesis by P i starvation in C. albicans opaque cells (but not white cells) may also be related to previous work on gene expression patterns in white versus opaque cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, C. albicans, which has retained the starvation response but also acquired the ability to robustly filament under a variety of nutrient-rich conditions, appears to be better adapted for colonization and infection of a wider range of host niches. A recent report that C. albicans opaque cells, which are mating competent, can undergo filamentation in response to distinct environmental cues also suggests that C. albicans further evolved cell type-specific filamentation for particular host niches (74).…”
Section: Discussionmentioning
confidence: 99%